Aphaenogaster graeca nova species (Hym: Formicidae) aus dem Olymp-Gebirge (Griechenland) und eine Gliederung der Gattung Aphaenogaster. - Schulz, Andreas (Contributions to Entomology = Beiträge zur Entomologie, 1994)
The ant species Aphaenogaster graeca n. sp. is described from the Olymp-Mountains in Greece. Descriptions are given for workers, females and males. The species is morphologically related to A. cf. kurdica from Iran and the Kaukasus region and the A. splendida from different mediterranean countries. It is closely related to A. gibbosa from France and the Iberian Peninsula, too. - The following combinations of characters of the workers avard confusions with other european species: The mesonotum slightly raises over the pronotum, with two transverse elevations. The caput is formed in the way of species in the A. subterranea group. The Scapus surpasses the occipital margin in 1/5 of length. Colour dark testaceus-brown. Sculpture of the head strong, with reticulate rugae, between the rugae punctuations. Integument nearly matt without shining integument. The male is morphologically related to A. muelleriana. - Additional it is made an attempt to build species-groups in the genus Aphaenogaster.Nomenclatural Actsgraeca Schulz, 1994 (Aphaenogaster), spec. n.